Identification of rare anti-f alloantibody in a tertiary care center in India - Gunjan Bhardwaj; Ashish Tewari; Deepak Tiwari; Sanjay Vishwakarma (Asian Journal of Transfusion Science)
A 68-year-old male known follow-up patient of nonalcoholic steatohepatitis and carcinoma stomach was admitted to hospital for further management. The patient was planned for radical gastrectomy and required two units of packed red blood cell (PRBC), due to low hemoglobin of 6.6 g/dl. The patient blood grouping and antibody screening (ABS) were done. Patient ABS was positive. On antibody identification, using eleven-cell identification panel, resolve Panel A (Ortho Clinical Diagnostics, Johnson and Johnson, USA), “anti-f” alloantibody was identified in the patient sample. Select cells, from another resolve panel were used to rule out remaining antibodies. Anti-f antibody is produced due to the exposure of “f antigen.” Anti-f antibody can cause hemolytic disease of fetus and new-born and possible hemolytic transfusion reactions. At our center, we successfully transfused two units of anti-human globulin compatible and “c-negative” units, to the patient without any adverse reactions. Thus, the patient having anti-f antibody can be managed by transfusing “c-negative” or “e-negative” PRBC units or units lacking both the “c” and “e” antigens.